(untitled) (Research, Society and Development, 2021)
Objective: To analyze weight gain and nutritional status of pregnant women with diabetes mellitus gestational. Methodology: This is a descriptive, cross-sectional study, conducted from August to December 2020, in a high-risk pregnancy reference service in Pernambuco. Information on anthropometric, socioeconomic, demographic, clinical, obstetric and lifestyle data were collected. To statistical analysis the Pearson’s Chi-Square and Fisher’s Exact tests, were performed, when applicable, at 5% significance level. Results: 101 high-risk pregnant women were studied, with mean age 30,73 ± 6,29, most (79,2%) with previous overweight and with weight gain during gestation (85,1%). Excessive weight gain was prevalent (45,3%), revealing positive association with current nutritional status. The presence of pathologies associated with DMG was the only obstetric data which showed a significative association with previous and current nutritional status and gestational weight gain, regardless of the type of comorbidities. Conclusion: Excess weight gain was prevalent, as well as the frequency of overweight before and during pregnancy, which shows the importance of nutritional monitoring in patients with gestational diabetes mellitus.